Pendidikan Pesantren untuk Perdamaian Dunia - Chairudin, Mochamad (Proceedings of Annual Conference for Muslim Scholars, 2022)
Typologically, Islamic boarding school education has had an influence on civilization in Indonesia. Islamic boarding schools in Indonesia play three important roles in Islamic civilization. First, Islamic boarding schools function as centers for religious studies that give birth to Muslim scholars, so that they can develop Islamic teachings. Second, is the act of openness to modernization by considering selectivity acts that function as a filter. Third, pesantren creates a link to connect religion, culture, and local wisdom. Islamic Boarding School as a miniature of peace, is a place that aims to form a community of rahmatan lil alamin, a moderate friendly Islam in a plural and multicultural society so that it can create world peace Keywords: